Shipment of Cyanobacteria by Agarose Gel Embedding (SCAGE)—A Novel Method for Simple and Robust Delivery of Cyanobacteria - Phillipp Fink; Jong-Hee Kwon; Karl Forchhammer (Bio-Protocol)
In modern science, the exchange of scientific material between different institutions and collaborating working groups constitutes an indispensable endeavor. For this purpose, bacterial strains are frequently shipped to collaborators to advance joint research projects. Bacterial strains are usually safely shipped as cultures on solid medium, whereas the shipment of liquid cultures requires specific safety measures due to the risk of leakage. Cyanobacterial cultures are frequently maintained as liquid stock cultures, and this problem typically arises. This protocol describes a new method for the shipment of liquid cyanobacterial stock cultures by agarose gel embedding (SCAGE). More specifically, a cyanobacterial culture is mixed with low-melting agarose and cast into sterile plastic bags, resulting in a thin, solid cyanobacterial agarose gel (cyanogel) that can be easily shipped. After delivery, subsequent regeneration of the cyanogel material in liquid media results in full recovery of the examined bacterial strains. Thus, the packaging method devised in the present study comprises an innovative technique to facilitate the shipment of bacterial strains, whilst eliminating previously encountered issues like cell culture leakage.